Parental warmth interacts with several genes to affect executive function components: a genome-wide environment interaction study - Chunhui Chen (BMC Genetics, 2020)
Abstract Background Executive function (EF) is vital to human beings. It has been linked to many genes and family environmental factors in separate studies, but few studies have examined the potential interactions between gene(s) and environmental factor(s). The current study explored the whole genome to identify SNPs, genes, and pathways that interacted with parental warmth (PW) on EF. Results Nine EF tasks were used to measure its three components (common EF, updating, shifting) based on the model proposed by Miyake et al. (2000). We found that rs111605473, LAMP5, SLC4A7, and LRRK1 interacted significantly with PW to affect the updating component of EF, and the GSE43955 pathway interacted significantly with PW to affect the common EF component. Conclusions The current study is the first to identify genes that interacted with PW to affect EF. Further studies are needed to reveal the underlying mechanism.